MODERN LIFESTYLE AND DRY EYE DISEASE: A NARRATIVE REVIEW OF MODIFIABLE RISKS AND PREVENTIVE STRATEGIES - Daria Julia Makowska-Woszczyk; Julia Groszewska; Agata Mytych; Michał Romaniuk; Agata Rapior; Kinga Lubomska; Patrycja Jagura; Jan Romaniuk; Marta Dziedziak; Łukasz Nosek (International Journal of Innovative Technologies in Social Science, 2025)
Background: Dry eye disease (DED) is a multifactorial ocular-surface disorder characterized by loss of tear-film homeostasis, resulting in ocular discomfort, visual disturbances, and progressive surface damage. While intrinsic factors such as age, sex, autoimmune disease, and systemic medications influence susceptibility, lifestyle and environmental determinants—including prolonged screen time, poor sleep, contact-lens wear, smoking, and suboptimal diet—have emerged as important, modifiable contributors to disease onset and severity. Addressing these factors is critical for effective prevention and management.Methods: This narrative review synthesizes evidence from PubMed, Scopus, and Web of Science (1990–2025) on associations between lifestyle behaviors and DED. Eligible studies included randomized controlled trials, cohort and cross-sectional studies, and systematic reviews published in English. Emphasis was placed on identifying modifiable behaviors that impact tear-film stability, ocular-surface inflammation, and symptom burden.Results: Evidence indicates that extended digital-screen use, disrupted sleep, contact-lens wear, and smoking increase DED risk and exacerbate symptoms. Conversely, interventions targeting modifiable behaviors—such as scheduled visual breaks, hydration, improved sleep hygiene, eyelid hygiene, smoking cessation, and nutritional optimization—are associated with improved tear-film stability, reduced inflammation, and symptomatic relief.Conclusions: Lifestyle behaviors play a critical role in DED pathogenesis and progression. Integrating behavioral counseling into clinical practice and public-health strategies provides a low-cost, patient-empowering approach to reduce disease burden and improve ocular-surface health.